The Influence of Leadership, Work Motivation, and Work Discipline on Employee Performance at RSGM Unjani - Ermanawati, Widdy Ayu Utami; Saputro, Arie Hendra (Dinasti Publisher, 2025)
A hospital is a health service system that provides services to the community which include medical services, medical support and care services. RSGM Unjani is a teaching hospital that has developed and provides public services and collaborates with BPJS Health. However, in the midst of its development, there are still many people who are not satisfied with the services provided, this is caused by poor service ad employee performance that is not yet optimal. The aim of research is to determine the influence of leadership, work motivation and work discipline on employee performance. The method used in this research is a quantitative method with a descriptive and verification approach with a total sampling technique on 66 employees at RSGM Unjani are categorized as high. The research result show that leadership has no significant effect on performance, work motivation has significant effect and work discipline has significant effect on performance. The influence of leadership, work motivation, and work discipline has coefficient of determination of 49,90% and the remaining 51,10%is influenced by other factors not studied.